Modelling height-diameter relationship for Pinus wallichiana trees for Lete and Kunjo of Mustang district - Wagle, B. H.; Sharma, R. P. (Banko Janakari, 2013)
Quantifi cation of height-diameter relationship helps in better understanding of stand dynamics. Height-diameter models can be used as necessary inputs to growth and yield models and growth simulation systems. The researchers developed height-diameter models with 364 Blue pine (Pinus wallichiana) tree data from Lete and Kunjo Village Development Committees (VDCs) of Mustang district. Eighteen non-linear models were calibrated, among which, Weibull model described the largest proportion of height variation (R2 adj = 0. 9362). Gunary and Chapman-Richards’ models also appeared almost identical to Weibull model in terms of fi t statistics and graphical appearance. The researchers recommend Weibull model for predicting total heights of Blue pine trees for the VDCs covered by the study. DOI: http://dx.doi.org/10.3126/banko.v21i2.9125 Banko Janakari Vol. 21, NO. 2, 2011 Page: 13-23 Uploaded date: 10 November, 2013